229k views
5 votes
Solve for x
in the equation x^2-12x+36=90

User TheMI
by
5.1k points

2 Answers

5 votes

Answer:

Using the identity rule:


(a-b)^2 = a^2-2ab+b^2

Given the equation:


x^2-12x+36 = 90

Rewrite the above equation as:


x^2-2 \cdot x \cdot 6+6^2 = 90

Apply the identity rule:


(x-6)^2 = 90

Take square root to both sides we have;


x-6 = \pm √(90)

Add 6 to both sides we have;


x = 6\pm √(90)

or


x = 6 \pm 3√(10)

Therefore, the value of x are:


6+3√(10) and
6-3√(10)

User Roman Nazarkin
by
5.1k points
5 votes
This can be rewritten as
(x -6)² = 90 . . . . . the left side is already a perfect square
x -6 = ±√90 . . . . . take the square root
x = 6 ±3√10 . . . . add 6
User Ulu
by
5.3k points